Computer Simulation of Hemodynamic Parameter Changes by Mechanical Ventilation and Biventricular Circulatory Support - Darowski, M.; Lazzari, De C.; Ferrari, G.; Clemente, F.; Guaragno, M. (Methods of Information in Medicine, 2000)
When a Bi-Ventricular Assist Device (BVAD) is used in conjunction with mechanical ventilation (MV) of the lungs with positive intrathoracic pressure (Pt), the latter influences hemodynamics. The aim of our study was to assess the simultaneous influence of BVAD and MV on hemodynamics. We assumed ventricular pathological conditions as reduced elastances and increased rest volumes. Peripheral systemic arterial resistance was assumed to have different values. Data were obtained by computer simulation. Trends in main hemodynamic variables were compared with clinical data from literature. Simulation showed that systemic venous, pulmonary arterial and left atrial pressures are very sensitive to Pt (-2 to 5 mmHg).
Keywords: Computer Simulation; Biventricular Assist Device; Mechanical Ventilation; Hemodynamics